Revision of the Tomoderinae (Coleoptera: Anthicidae). Part III. New species and records of Macrotomoderus Pic, 1901 from China and a key to the Palaearctic species - Telnov , Dmitry (European Journal of Taxonomy, 2022)
Descriptions of the following 23 species of Macrotomoderus Pic, 1901 new to science, from continental China, are provided as an addition to the recently published review of the genus from China and Taiwan (Telnov 2018): M. angelinii, M. belousovi, M. bicrispus, M. boops, M. bordonii, M. dali, M. daxiangling, M. femoridens, M. hajeki, M. hartmanni, M. hengduan, M. imitator, M. kabaki, M. korolevi, M. lapidarius, M. muli, M. palaung, M. similis, M. tenuis, M. transitans, M. truncatulus, M. usitatus, and M. wudu spp. nov. Additional records are provided for some poorly known species. The identification key to the species of Macrotomoderus from China, the Japanese Archipelago, and Taiwan is herewith significantly supplemented and updated. Biogeographical peculiarities and altitudinal gradient of Macrotomoderus distribution in continental China are briefly discussed.